The Teaching of Anions and Cations with the Educational Set of Ions - Yenıkalayci, N.; Çelikler, D.; Aksan, Z. (Sakarya University editor@tojet.net, 2017)
Educational set of ions (ESI) is a card game that can be played with a group of 4. The reason why this game is designed is teaching names and formulas of anions and cations that would form a basis to write and term chemical formulas of the compounds which it is one of the most important subjects of chemistry. This game is prepared for students who study in different grades of education considering the subject on chemical compounds involving anion and cation teaching within the scope of chemistry lesson at high school and university. The game is discusses in 3 steps and these are “contents of the game set, playing the game and rules, and evaluation of the game results”. Pilot scheme conducted in development step of the game was performed with 49 students in total who studied in Science Teaching, Chemical Engineering, Food Engineering, Pharmacy and took lesson of General Chemistry. As a result of the pilot scheme, ESI was put into final form by making arrangements as regards decreasing amount of students in the group, having students sitting in a round, designing answer sheets as reusable in press printed to prevent paper wastage and playing the game by gathering the cards couldn’t be written by students. © The Turkish Online Journal of Educational Technology.
Keywords: Anion; Card Game; Cation; Chemical Formula; Ion; Training Set